Cover Feature: Charge‐Tagged N‐Heterocyclic Carbenes (NHCs): Revealing the Hidden Side of NHC‐Catalysed Reactions through Electrospray Ionization Mass Spectrometry (ChemPlusChem 2/2021). Issue 2 (23rd December 2020) - Salvitti, Chiara; Chiarotto, Isabella; Pepi, Federico; Troiani, Anna
Abstract : The Cover Feature shows the use of charge‐tagging to assess the chemistry of N ‐heterocyclic carbenes (NHCs) by electrospray ionization mass spectrometric (ESI‐MS) techniques. The insertion of positive or negative charged groups into the molecular scaffold allows the exploitation of mass spectrometry to intercept transient ionic species. The NHCs' intrinsic reactivity and their involvement in important chemical transformations have been highlighted in the Minireview by Anna Troiani, Chiara Salvitti, and co‐workers .